Participatory Management of Muscles Strengthening of Core Stability and Lower Extremity to Reduce of Premenstrual Syndrome - Diono, Hartono (European Journal of Applied Sciences, 2018)
Competence to reduce of premenstrual syndrome must be have each student, so physically and psychologically able to do activities Tridharma Colleges well. One of the efforts that can reduce of premenstrual syndrome is doing muscles strengthening of core stability and lower extremity. The purpose of the research to prove that participatory management model of muscles strengthening of core stability and lower extremity can reduce of premenstrual syndrome for students of Cilacap Graha-Mandiri Midwifery Academy, in Central Java. The research used was pre-experimental quantitative research design with form of One-Group Pretest-Postest Design. The results of t-test of significance of the score obtained related 0.000 < 0.05, or tcount = 16.741 > ttable α 0.05, df 34 = 2.031; therefore H0 is rejected and Ha is accepted. It’s meaning Participatory management model of muscles strengthening of core stability and lower extremity can reduce of premenstrual syndrome for students of Cilacap Graha-Mandiri Midwifery Academy, in Central Java. Conclusion, participatory management model of muscles strengthening of core stability and lower extremity can reduce of premenstrual syndrome for students of Cilacap Graha-Mandiri Midwifery Academy, in Central Java.